Adat Law as a Foundation for Advancing Indonesian Agrarian Law to Maximise Societal Welfare - Firman Muntaqo; Febrian Febrian; Alip Dian Pratama (Faculty of Law, Sriwijaya University, Indonesia, 2024)
The evolution of agrarian law in Indonesia, particularly land law, must adhere to the constitutional mandate of promoting the welfare of the populace. This subject is compelling because existing studies predominantly address the legal-formal dimensions of customary land law without adequately examining its practical implications for public welfare. This research investigates whether the development of Indonesian land law is in accordance with the Agrarian Law and explores how to formulate legal frameworks that mitigate land disputes and conflicts related to the utilisation of Ulayat Land for development purposes. The objective is to present alternative recommendations for resolving national agrarian law issues, often diverging from constitutional directives. Employing a normative research method, this study draws on both legal and non-legal materials through philosophical, legislative, historical, conceptual, comparative, and futuristic lenses. The findings reveal that the current development of national agrarian law does not fully align with the Agrarian Law's mandate to enhance the welfare of the Indonesian people. Therefore, this research offers alternative legislative methods aimed at producing agrarian legal instruments that more effectively promote the prosperity of the Indonesian population.